2016
DOI: 10.1039/c6ta01929c
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt phosphate nanoparticles decorated with nitrogen-doped carbon layers as highly active and stable electrocatalysts for the oxygen evolution reaction

Abstract: We develop a facile method to prepare cobalt phosphate nanoparticles coated by N-doped carbon layers for highly active and stable OER electrocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
153
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(159 citation statements)
references
References 43 publications
6
153
0
Order By: Relevance
“…The η 10 for CoPPi nanobelts, nanoleaves, and nanorhombuses are determined to be 371, 390, and 424 mV, respectively, higher than that of nanowires. In terms of η 10 , the catalytic performance of our CoPPi nanowires outperforms the reported coralloid Co 2 P 2 O 7 nanocrystal carbon composite catalyst CL‐Co 2 P 2 O 7 @C (397 mV) and most of CoPi catalysts studied in alkaline media, such as mesoporous CoPi (380 mV), Co 3 (PO 4 ) 2 (≈430 mV), and even comparable to that of CoPi@C composite, for example, CC/NPC/CP (430 mV), Co 3 (PO 4 ) 2 @N‐C (317 mV), and CoPi/PCDs (350 mV) …”
mentioning
confidence: 68%
See 1 more Smart Citation
“…The η 10 for CoPPi nanobelts, nanoleaves, and nanorhombuses are determined to be 371, 390, and 424 mV, respectively, higher than that of nanowires. In terms of η 10 , the catalytic performance of our CoPPi nanowires outperforms the reported coralloid Co 2 P 2 O 7 nanocrystal carbon composite catalyst CL‐Co 2 P 2 O 7 @C (397 mV) and most of CoPi catalysts studied in alkaline media, such as mesoporous CoPi (380 mV), Co 3 (PO 4 ) 2 (≈430 mV), and even comparable to that of CoPi@C composite, for example, CC/NPC/CP (430 mV), Co 3 (PO 4 ) 2 @N‐C (317 mV), and CoPi/PCDs (350 mV) …”
mentioning
confidence: 68%
“…Interestingly, CoPPi nanowires electrode exhibits a Tafel slope of 54.1 mV dec −1 , substantially lower than that of Ir/C, and also the CoPPi nanobelts (57.9 mV dec −1 ), nanoleaves (81.6 mV dec −1 ), and nanorhombuses (118.5 mV dec −1 ), suggesting the favorable OER kinetics of CoPPi nanowires . Note that this value is lower than the reported CL‐Co 2 P 2 O 7 @C (70 mV dec −1 ) and the other CoPi based catalysts, for example, mesoporous CoPi (58.7 mV dec −1 ), Co 3 (PO 4 ) 2 @N‐C (62 mV dec −1 ), and CC/NPC/CP (80 mV dec −1 ) . In order to estimate the intrinsic activity, turnover frequency (TOF) was calculated by assuming that all catalysts were involved in OER processes (see the Supporting Information) .…”
mentioning
confidence: 74%
“…Achieving low overpotential for the conventionally sluggish OER near neutral pH, demands a combination of highly dense and uniformly accessible active sites. Further, the surface‐reconstruction induced formation of amorphous layer would enhance the four‐electron OER . Such reconstruction of the surface has been observed to transform the crystalline phases to catalytically active amorphous domains resulting in high OER activity .…”
mentioning
confidence: 99%
“…reported that cobalt phosphate nanoparticles decorated with nitrogen‐doped carbon layers (Co 3 (PO 4 ) 2 @N−C), which were synthesized via hydrothermal method that O‐phospho‐DL‐serine was added to water/ethanol solution (1 : 1) consisting Cobalt(II) acetate. The homogeneous mixture solution was transferred to Teflon‐lined stainless steel autoclave and maintained at 200 °C for 24 h …”
Section: Syntheses Of Phosphate‐based Electrocatalystsmentioning
confidence: 99%